What is the Real Story of China's "Hidden Debt"? - Deborah Brautigam; Yufan Huang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
On September 29, 2021, AidData, a research lab at William & Mary, released a detailed overview of their new data on China's global lending, "Banking on the Belt and Road." The report has generated much commentary. In this briefing paper, Deborah Brautigam and Yufan Huang examine the data underpinning the AidData conclusions. While they agree with many of AidData's points, the authors' own analysis of the data puts a very different spin on their headline conclusions. Brautigam and Huang argue that by providing averages, not discussing outliers, and allocating the entire Chinese loan for joint ventures to only the host government partner, the AidData report is unduly alarmist.
Keywords: 330